Current treatment options for gastroenteropancreatic neuroendocrine tumors with a focus on the role of lanreotide - Beata Kos-Kudła; Jarosław Ćwikła; Marek Ruchała; Alicja Hubalewska-Dydejczyk; Barbara Jarzab; Jolanta Krajewska; Grzegorz Kamiński (Contemporary Oncology)
Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) are a large and very diverse group of neoplasms. Clinical presentation of NETs depends on the site of the primary tumor and whether the tumor is functioning (i.e., secreting peptides or neuroamines that produce symptoms). The diagnosis of GEP-NET is further complicated by symptomatic differences that occur depending on the type of secreted peptide or neuroamine. Due to their heterogeneity and unique characteristics, early diagnosis of GEP-NETs is difficult, which increases the likelihood of metastatic disease and reduces the scope of therapeutic possibilities. Thus, a multidisciplinary approach for the treatment of GEP-NETs is necessary. This review is the result of presentations that were delivered during an expert meeting on the treatment of GEP-NETs supported by Ipsen. We summarize the current knowledge on the epidemiology, incidence, diagnosis, and treatment of GEP-NETs. We examined the role of the somatostatin analog (SSA) lanreotide and the impact of the data from the recently published, randomized, double-blind, placebo -controlled CLARINET study (Controlled study of Lanreotide Antiproliferative Response In Neuroendocrine Tumors) on disease management. We also review the recent treatment options and recommendations for GEP-NETs.